Assessing the Creative Thinking Level of In-Service Chemistry Teachers Using a Case Study Test - Salirawati, Das; Primastuti, Metridewi; Priyambodo, Erfan (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2024)
In the 21st century is an urge that teachers are not only required to change teaching methods but also have a role and responsibility to be able to motivate students' reasoning and logic to think critically, creatively, and innovatively. This study was conducted to assess the level of creative thinking skills of high school chemistry teachers in one of the districts/cities in Yogyakarta Province. As a survey with a quantitative approach, this study involved 24 in-service chemistry teachers as respondents. All of the population became the respondents in this study so that saturated sampling technique was applied. Creative thinking skills were measured using the creative thinking skill test (CTST). The results of the Aiken content analysis validity show that the instrument was suitable to apply with a score of 0.92. Six out of 10 test items are empirically valid with a reliability value of 0.697. CTST was filled in by respondents at the chemistry teachers' meeting forum. Data analysis was carried out using descriptive statistics to answer the categories of in-service chemistry teachers' creative thinking. Based on the results of CTST, it was 3.20 related to a sufficient creative thinking level category. The current research result suggests professional training for teachers to optimize their creativity in chemistry teaching strategy.